Labor migration, remittances, and human capital accumuation in Nepal - KHAN, Viktoriya (KDI School, 2018)
Labor migration in Nepal is perpetuated by the existence of a porous border between Nepal and India, which is the gate to the outer world for Nepalese formal and informal labor migrants. For decades Nepal has continuously been one of the countries with the highest inflow of remittances as a percentage of GDP, reaching 31% in 2016 (World Bank, 2018). This paper investigates the impact of remittances on human capital accumulation in recipient households in Nepal, using a comprehensive nationwide Nepal Living Standards Survey of 1996, 2003 and 2010. The study addresses the endogeneity of remittances and human capital by adopting instrumental variable two-stage least squares methodology. International remittances are predicted by historical migration rates, which are extracted from Nepal Population Census of 1991. The main results show that there is a statistically significant, positive impact of remittances on educational expenditures, private schooling and private tuition.
Thesis(Master) --KDI School:Master of Public Policy,2018